Citrinin stimulated heterophil extracellular trap formation in chickens. (December 2022) - Chen, Yichun; Ye, Yingrong; Wu, Hanpeng; Wu, Zhikai; Li, Peixuan; Fu, Yiwu; Sun, Youpeng; Wang, Xia; Wang, Jingjing; Yang, Zhengtao; Zhou, Ershun
Abstract: Citrinin (CTN), a secondary fungal metabolite produced by several Aspergillus, Penicillium, and Monascus genera species, is a toxin with a wide range of biological activities. Neutrophil extracellular traps represent a novel potential mechanism of the neutrophil response to foreign matters, and chicken heterophils can release similar heterophil extracellular traps (HETs). In this study, we aimed to investigate the effect of CTN on HET formation. Density gradient centrifugation was used to isolate chicken peripheral blood heterophils, and then immunofluorescence was used to observe the effects of CTN on HET formation. The mechanisms of HET formation were analyzed using pharmacological inhibitors and quantification of extracellular DNA, and the production of reactive oxygen species was detected with a fluorescent probe. Our results revealed that CTN (50–400 μM) had no cytotoxic effect on heterophils. CTN exposure induced the release of HETs composed of chromatin decorated with histones and elastase, and CTN-triggered HETs were dose- and time-dependent to some extent. Furthermore, CTN increased ROS production and activated p38 and ERK1/2 signaling pathways in heterophils. However, inhibition of the p38 signaling pathway, ERK1/2 signaling pathway, and NADPH oxidase pathway did not block HET formation induced by CTN. Inhibition of peptidyl arginine deiminase 4 (PAD4) enzyme and P2×1 receptor decreased HET formation after CTN stimulation, suggesting that HET formation exposed to CTN was mediated by PAD4 and P2×1 receptor. In conclusion, these findings may suggest a canonical mechanism relevant to the innate immunity caused by mycotoxins in chickens. Highlights: Citrinin induced heterophil extracellular traps (HETs) in heterophils. Citrinin-induced HETs was composed of DNA decorated with H3 and NE. Citrinin activated p38 and ERK1/2 signaling pathways in heterophils. Citrinin-induced HETs was a PAD4 enzyme and P2×1 receptor-mediated process.